2009
DOI: 10.1002/anie.200805843
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Catalytic Promiscuity for Chemically Distinct Reactions

Abstract: High catalytic proficiencies observed for the native and promiscuous reaction of the Pseudomonas aeruginosa arylsulfatase (PAS; the picture shows transition states of the two substrates with corresponding binding constants K(tx)) suggest that the trade-off between high activity and tight specificity can be substantially relaxed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
82
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 32 publications
3
82
0
Order By: Relevance
“…The x-ray structure of BcPMH confirms that it is structurally and mechanistically closely related to arylsulfatases and also, albeit more distantly, to AP and nucleotide phosphodiesterase (11,13). These three enzymes catalyze at least two reactions besides their native activity that are the native reactions of another family member (14)(15)(16)(17)(18)(19). BcPMH promotes all native reactions of these three enzymes, making catalytic promiscuity a widespread feature of this superfamily.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The x-ray structure of BcPMH confirms that it is structurally and mechanistically closely related to arylsulfatases and also, albeit more distantly, to AP and nucleotide phosphodiesterase (11,13). These three enzymes catalyze at least two reactions besides their native activity that are the native reactions of another family member (14)(15)(16)(17)(18)(19). BcPMH promotes all native reactions of these three enzymes, making catalytic promiscuity a widespread feature of this superfamily.…”
Section: Discussionmentioning
confidence: 63%
“…PMH is a member of the alkaline phosphatase (AP) superfamily that encompasses structurally related enzymes known to hydrolyze phosphate monoesters and diesters and sulfate monoesters (13). Several members of the AP superfamily show catalytic promiscuity, and in some cases the promiscuous reactions are the native activities of other superfamily members (14)(15)(16)(17)(18)(19).BcPMH catalyzes the hydrolysis of a total of six different substrate classes, four of which correspond to activities seen in the AP superfamily. The collection of substrate classes, for which rate accelerations between 10 7 and 10 19 are observed, encompasses large variations in charge, the reaction center, size, hydrophobicity, reactivity, and nature of the TS of the uncatalyzed reaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is well known that a given enzyme is able to catalyze a specific reaction efficiently, some unexpected experimental results have indicated that many enzymes are catalytically promiscuous; i.e., they have the ability to catalyze distinctly different reactions (Copley, 2003;Khersonsky et al, 2006;Hult and Berglund, 2007). Many instances of this phenomenon have recently been reported (Babtie et al, 2009;Hasnaoui-Dijoux et al, 2008;Lou et al, 2008;Olguin et al, 2008;Sharma et al, 2009;Svedendahl et al, 2008;Taglieber et al, 2007;Xu et al, 2007).…”
Section: Introductionmentioning
confidence: 94%
“…In contrast, catalytic promiscuous enzymes carry out a secondary reaction that results in a chemical transformation different from that catalyzed with its canonical substrate [11]. In this context, catalytic promiscuity may become less efficient than the primary reaction, such as the secondary phosphoserine phosphatase activity of HisB (UniProt:P06987) and , whereas the secondary reaction of hydrolysis of bis(4-nitrophenyl) phosphate has a k cat /K M of 2.5 × 10 5 M −1 s −1 [16]. These examples show that the rate constant for many promiscuous reactions are within the range of physiologically relevant reactions, which k cat /K M round between 10 3 and 10 5 M −1 s −1 as observed in metabolic enzymes [11].…”
Section: How Many Kinds Of Promiscuity Are There?mentioning
confidence: 99%